Method for improving corrosion resistance of aluminum anode oxide film

Through laser purification and repair, quenching treatment and specific raw material ratio in the electrolyte, the problems of aluminum anodized film in the coordination improvement of corrosion resistance, wear resistance and adhesion properties are solved, and the film's voltage resistance and use efficiency are significantly improved.

CN119640362AInactive Publication Date: 2025-03-18HAINENG (LIAONING) ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510180786.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When the existing aluminum anodized film improves corrosion resistance, it is difficult to maintain wear resistance and base layer adhesiveness, and the voltage resistance is poor, which limits the efficiency of the product.

Method used

The surface of the aluminum anode is treated with laser purification and repair technology, followed by quenching, and coated in the electrolyte. Sulfuric acid, silica sol, oxalic acid, equilibrium agent and modified co-adjusting agent are added to the electrolyte to coordinate and improve the performance of the oxide film.

Benefits of technology

It significantly improves the corrosion resistance, wear resistance and adhesive properties of aluminum anodized film, while improving the voltage stability of the film products and improving the product's use efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum anode treatment, in particular to a method for improving the corrosion resistance of an aluminum anode oxide film, which comprises the following steps that the surface of an aluminum anode is purified by laser, specifically, a laser emitter focuses a laser beam on the surface of the aluminum anode to move, clean and purify, the laser emission average power of the laser emitter is 300W, the adjustable range of the pulse frequency is 2000KHz, and the laser emission average power of the laser emitter is 300W; the pulse width is 300 ns, and the single pulse energy is 50-100 mJ. The aluminum anode oxide film is subjected to surface purification treatment by adopting a laser transmitter, then cladding repair, quenching improvement and electrolyte coating treatment to obtain an oxide film product, and the oxide film product has coordinated improvement of corrosion resistance, wear resistance and adhesive strength, and meanwhile, the film product is remarkable in voltage-resistant stability effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum anode treatment, and in particular to a method for improving the corrosion resistance of an aluminum anodized film. Background Art

[0002] In aluminum electrolysis production, the consumption of carbon anode is one of the main factors affecting the cost. Carbon anode not only participates in the electrochemical reaction in aluminum electrolysis production, but also plays a conductive role. Therefore, in aluminum electrolysis production, the stable state of carbon anode affects the stable operation of the electrolytic cell, and also affects the quality of raw aluminum, current efficiency, power consumption and technical and economic indicators.

[0003] In order to improve the corrosion resistance of the existing aluminum anodized film, the wear resistance of the product and the adhesion of the base layer are easily affected. It is difficult to achieve coordinated improvements in corrosion resistance, wear resistance and adhesion of the product. At the same time, the voltage resistance stability of the film product is poor, which limits the product's use efficiency. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a method for improving the corrosion resistance of aluminum anodized film to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a method for improving the corrosion resistance of an aluminum anodized film, comprising the following steps: Step 1: Laser purifies the surface of the aluminum anode: the laser transmitter focuses the laser beam on the surface of the aluminum anode and moves it for cleaning and purification. The average power of the laser transmitter is 300W, the adjustable range of the pulse frequency is 2000KHz, the pulse width is 300ns, and the single pulse energy is 50~100mJ; Step 2: The aluminum anode purified in step 1 is repaired by using aluminum powder as raw material through powder spreading and laser scanning, with laser power of 650W, scanning spot diameter of 70um, scanning speed of 7000mm / s and scanning spacing of 0.2mm; Step 3: quench the aluminum anode repaired in step 2 at a quenching temperature of 150°C for 5 hours, then place the quenched aluminum anode in an electrolyte for coating, then take it out for water washing at a water washing temperature of 80°C, and finally quickly dry it at 100°C for 1 minute; The electrolyte comprises the following raw materials in parts by weight: 20-25 parts by weight of sulfuric acid, 7-11 parts by weight of silica sol, 6-9 parts by weight of balancing agent, 5-8 parts by weight of oxalic acid, 4-6 parts by weight of modifying co-compounding agent, and 15-20 parts by weight of water.

[0006] Preferably, the coating treatment uses an aluminum anode as an anode and an aluminum alloy plate as a cathode, and the ratio of the cathode to the anode area is 2:1, and the anodic coating oxidation is performed for 60 minutes at a temperature of 30°C and a direct current of 15-20An.

[0007] Preferably, the preparation method of the balancing agent is: S01: The graphene is first placed in a sufficient amount of 5% by mass hydrogen peroxide solution and stirred sufficiently, then washed with water and dried, and then stirred sufficiently in a sufficient amount of 4% by mass potassium permanganate solution, then washed with water and dried; S02: immersing the hydroxyapatite in a 3% yttrium nitrate solution having a mass fraction of 2 to 5 times the total amount of the hydroxyapatite and stirring sufficiently to obtain a hydroxyapatite solution; 1-3 parts by weight of sodium carboxymethyl cellulose, 1-2 parts by weight of silane coupling agent and 2-5 parts by weight of hydroxyapatite liquid are uniformly mixed, and then 2-3 parts by weight of sodium silicate solution are added and stirred continuously to obtain a modified liquid; S03: preheating the graphene dried in S01 to 65°C, and then immersing it in a modification liquid 3 to 5 times the total amount of graphene, stirring and modifying it, and after the stirring is completed, a modified graphene liquid is obtained; S04: The modified graphene liquid and the rare earth-doped nano-titanium dioxide modifier are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a balancing agent.

[0008] The balancing agent adopts graphene which is treated with hydrogen peroxide solution and potassium permanganate solution, and then preheated to optimize its activity energy. At the same time, it is improved and optimized by using a modifying liquid. The hydroxyapatite in the modifying liquid is treated with yttrium nitrate solution, and then blended with sodium carboxymethyl cellulose, silane coupling agent and sodium silicate solution. The raw materials in the modifying liquid are mutually adjusted to enhance the synergy and optimize the graphene improvement effect. Therefore, with graphene as the matrix, in the system, after electrolysis treatment, the performance coordination and performance stability of the aluminum anode film are enhanced. At the same time, the product performance is further enhanced by ball milling of a modifying agent doped with rare earth and prepared with nano titanium dioxide.

[0009] Preferably, the mass fraction of the sodium silicate solution is 3-6%; and the silane coupling agent is silane coupling agent KH550.

[0010] Preferably, the stirring speed of the stirring modification treatment is 350-400 r / min, and the stirring is for 1 hour.

[0011] Preferably, the preparation method of the rare earth-doped nano-titanium dioxide modifier is: The nano-titanium dioxide is first irradiated in a proton irradiation box for 10 to 15 minutes at an irradiation power of 350 W. After the irradiation is completed, the irradiated nano-titanium dioxide, lanthanum chloride solution and sodium stearate are prepared in a weight ratio of 3:5:1 to obtain a nano-titanium dioxide agent; 2-4 parts by weight of boron nitride and 1-3 parts by weight of cerium oxide are mixed and sintered to obtain a sintering agent. The sintering agent and nano-titanium dioxide agent are ultrasonically treated in a weight ratio of 2:5, and then filtered and dried to obtain a rare earth-doped nano-titanium dioxide modifier.

[0012] The modifier of rare earth-doped nano-titanium dioxide is prepared by proton irradiation of nano-titanium dioxide, blending with lanthanum chloride solution and sodium stearate, and adding boron nitride and cerium oxide to the system after sintering. The obtained modifier of rare earth-doped nano-titanium dioxide is coordinated with graphene, thereby further coordinating and improving the product and optimizing the performance stability of the product. Boron nitride and cerium oxide are mixed and filled into the nano-titanium dioxide system, and the product performance improvement effect is enhanced.

[0013] Preferably, the sintering temperature of the sintering treatment is 175-185° C., and the sintering time is 1 hour; the ultrasonic power of the ultrasonic treatment is 300-350W, and the ultrasonic treatment time is 20 minutes.

[0014] Preferably, the mass fraction of the lanthanum chloride solution is 3-5%.

[0015] Preferably, the preparation method of the modified synergistic agent is: S101: heat treating the carbon nanotubes at 210-220°C for 10 min, then cooling to 60°C at a rate of 1-3°C / min, and keeping the temperature; S102: preparing a 2-5% by weight sodium dodecylbenzene sulfonate solution and a 5% by weight chitosan solution; adding 2-4 parts by weight of the sodium dodecylbenzene sulfonate solution to 5-8 parts by weight of the chitosan solution, and then adding 2-5 parts by weight of alginate, and stirring thoroughly to obtain a coordinated solution; S103: The carbon nanotubes treated in S101 and the co-formulation liquid are stirred and treated in a weight ratio of 3:7, and then filtered and dried to obtain a modified co-formulation agent.

[0016] The modified synergistic agent is made of carbon nanotubes that are thermally modified to stimulate their active efficiency, and then the carbon nanotubes are synergized with a synergistic liquid obtained by sodium dodecylbenzene sulfonate solution, chitosan solution and alginate. The modified synergistic agent is coordinated and balanced by blending the raw materials in the synergistic liquid to enhance the effect of the coordinated balancing agent. The synergistic reinforcement effect of the two is significantly optimized and improved, and the performance of the product is further improved.

[0017] Preferably, the diameter of the carbon nanotubes is 1-2 nm.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The aluminum anodized film of the present invention is first subjected to surface purification treatment using a laser emitter, and then repaired by cladding, and improved by quenching at the same time, and then subjected to electrolyte plating treatment to obtain an oxide film product with coordinated improvements in corrosion resistance, wear resistance and adhesion, and at the same time, the voltage resistance stability of the film product is significantly improved, sulfuric acid is used in the electrolyte to cooperate with silica sol, oxalic acid and water, and a balancing agent and a modifying synergist are added to coordinate the two, and the product performance is significantly improved through the coordination and synergy between the raw materials. DETAILED DESCRIPTION

[0019] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] A method for improving the corrosion resistance of an aluminum anodized film according to the present embodiment comprises the following steps: Step 1: Laser purifies the surface of the aluminum anode: the laser transmitter focuses the laser beam on the surface of the aluminum anode and moves it for cleaning and purification. The average power of the laser transmitter is 300W, the adjustable range of the pulse frequency is 2000KHz, the pulse width is 300ns, and the single pulse energy is 50~100mJ; Step 2: The aluminum anode purified in step 1 is repaired by using aluminum powder as raw material through powder spreading and laser scanning, with laser power of 650W, scanning spot diameter of 70um, scanning speed of 7000mm / s and scanning spacing of 0.2mm; Step 3: quench the aluminum anode repaired in step 2 at a quenching temperature of 150°C for 5 hours, then place the quenched aluminum anode in an electrolyte for coating, then take it out for water washing at a water washing temperature of 80°C, and finally quickly dry it at 100°C for 1 minute; The electrolyte comprises the following raw materials in parts by weight: 20-25 parts by weight of sulfuric acid, 7-11 parts by weight of silica sol, 6-9 parts by weight of balancing agent, 5-8 parts by weight of oxalic acid, 4-6 parts by weight of modifying co-compounding agent, and 15-20 parts by weight of water.

[0021] The coating treatment in this embodiment uses an aluminum anode as the anode and an aluminum alloy plate as the cathode, and the ratio of the cathode to the anode area is 2:1. The anodic coating oxidation is performed for 60 minutes at a temperature of 30°C and a DC current of 15-20An.

[0022] The preparation method of the balancing agent of this embodiment is: S01: The graphene is first placed in a sufficient amount of 5% by mass hydrogen peroxide solution and stirred sufficiently, then washed with water and dried, and then stirred sufficiently in a sufficient amount of 4% by mass potassium permanganate solution, then washed with water and dried; S02: immersing the hydroxyapatite in a 3% yttrium nitrate solution having a mass fraction of 2 to 5 times the total amount of the hydroxyapatite and stirring sufficiently to obtain a hydroxyapatite solution; 1-3 parts by weight of sodium carboxymethyl cellulose, 1-2 parts by weight of silane coupling agent and 2-5 parts by weight of hydroxyapatite liquid are uniformly mixed, and then 2-3 parts by weight of sodium silicate solution are added and stirred continuously to obtain a modified liquid; S03: preheating the graphene dried in S01 to 65°C, and then immersing it in a modification liquid 3 to 5 times the total amount of graphene, stirring and modifying it, and after the stirring is completed, a modified graphene liquid is obtained; S04: The modified graphene liquid and the rare earth-doped nano-titanium dioxide modifier are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a balancing agent.

[0023] Preferably, the mass fraction of the sodium silicate solution is 3-6%; and the silane coupling agent is silane coupling agent KH550.

[0024] The stirring speed of the stirring modification treatment in this embodiment is 350-400 r / min, and the stirring is for 1 hour.

[0025] The preparation method of the rare earth-doped nano-titanium dioxide modifier of this embodiment is as follows: The nano-titanium dioxide is first irradiated in a proton irradiation box for 10 to 15 minutes at an irradiation power of 350 W. After the irradiation is completed, the irradiated nano-titanium dioxide, lanthanum chloride solution and sodium stearate are prepared in a weight ratio of 3:5:1 to obtain a nano-titanium dioxide agent; 2-4 parts by weight of boron nitride and 1-3 parts by weight of cerium oxide are mixed and sintered to obtain a sintering agent. The sintering agent and nano-titanium dioxide agent are ultrasonically treated in a weight ratio of 2:5, and then filtered and dried to obtain a rare earth-doped nano-titanium dioxide modifier.

[0026] The sintering temperature of the sintering treatment in this embodiment is 175-185° C., and the sintering time is 1 hour. The ultrasonic power of the ultrasonic treatment is 300-350 W, and the ultrasonic treatment time is 20 minutes.

[0027] The mass fraction of the lanthanum chloride solution of the present embodiment is 3-5%.

[0028] The preparation method of the modified synergistic agent of this embodiment is: S101: heat treating the carbon nanotubes at 210-220°C for 10 min, then cooling to 60°C at a rate of 1-3°C / min, and keeping the temperature; S102: preparing a 2-5% by weight sodium dodecylbenzene sulfonate solution and a 5% by weight chitosan solution; adding 2-4 parts by weight of the sodium dodecylbenzene sulfonate solution to 5-8 parts by weight of the chitosan solution, and then adding 2-5 parts by weight of alginate, and stirring thoroughly to obtain a coordinated solution; S103: The carbon nanotubes treated in S101 and the co-formulation liquid are stirred and treated in a weight ratio of 3:7, and then filtered and dried to obtain a modified co-formulation agent.

[0029] The diameter of the carbon nanotubes in this embodiment is 1-2 nm.

[0030] Example 1 A method for improving the corrosion resistance of an aluminum anodized film according to the present embodiment comprises the following steps: Step 1: Laser purifies the surface of the aluminum anode: the laser transmitter focuses the laser beam on the surface of the aluminum anode and moves it for cleaning and purification. The average power of the laser transmitter is 300W, the adjustable range of the pulse frequency is 2000KHz, the pulse width is 300ns, and the single pulse energy is 50mJ; Step 2: The aluminum anode purified in step 1 is repaired by using aluminum powder as raw material through powder spreading and laser scanning, with laser power of 650W, scanning spot diameter of 70um, scanning speed of 7000mm / s and scanning spacing of 0.2mm; Step 3: quench the aluminum anode repaired in step 2 at a quenching temperature of 150°C for 5 hours, then place the quenched aluminum anode in an electrolyte for coating, then take it out for water washing at a water washing temperature of 80°C, and finally quickly dry it at 100°C for 1 minute; The electrolyte comprises the following raw materials in parts by weight: 20 parts by weight of sulfuric acid, 7 parts by weight of silica sol, 6 parts by weight of balancing agent, 5 parts by weight of oxalic acid, 4 parts by weight of modifying co-forming agent, and 15 parts by weight of water.

[0031] The coating treatment in this embodiment uses an aluminum anode as the anode and an aluminum alloy plate as the cathode, and the ratio of the cathode to the anode area is 2:1. The anodic coating oxidation is performed for 60 minutes at a temperature of 30°C and a DC current of 15-20An.

[0032] The preparation method of the balancing agent of this embodiment is: S01: The graphene is first placed in a sufficient amount of 5% by mass hydrogen peroxide solution and stirred sufficiently, then washed with water and dried, and then stirred sufficiently in a sufficient amount of 4% by mass potassium permanganate solution, then washed with water and dried; S02: immersing the hydroxyapatite in a 3% yttrium nitrate solution with a mass fraction twice the total amount of the hydroxyapatite and stirring thoroughly to obtain a hydroxyapatite solution; 1 part by weight of sodium carboxymethyl cellulose, 1 part by weight of silane coupling agent and 2 parts by weight of hydroxyapatite solution are uniformly mixed, and then 2 parts by weight of sodium silicate solution are added and stirred continuously to obtain a modified solution; S03: preheating the graphene dried in S01 to 65°C, and then immersing it in a modification liquid 3 times the total amount of the graphene, stirring and modifying it, and after the stirring is completed, a modified graphene liquid is obtained; S04: The modified graphene liquid and the rare earth-doped nano-titanium dioxide modifier are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a balancing agent.

[0033] The mass fraction of the sodium silicate solution is 3%; the silane coupling agent is silane coupling agent KH550.

[0034] The stirring speed of the stirring modification treatment in this embodiment is 350 r / min, and the stirring is for 1 hour.

[0035] The preparation method of the rare earth-doped nano-titanium dioxide modifier of this embodiment is as follows: The nano-titanium dioxide was first irradiated in a proton irradiation box for 10 minutes at an irradiation power of 350W. After the irradiation was completed, the irradiated nano-titanium dioxide, lanthanum chloride solution and sodium stearate were prepared in a weight ratio of 3:5:1 to obtain a nano-titanium dioxide agent; 2 parts by weight of boron nitride and 1 part by weight of cerium oxide are mixed and sintered to obtain a sintering agent. The sintering agent and nano-titanium dioxide agent are ultrasonically treated in a weight ratio of 2:5, and then filtered and dried to obtain a rare earth-doped nano-titanium dioxide modifier.

[0036] The sintering temperature of the sintering treatment in this embodiment is 175° C., and the sintering time is 1 hour; the ultrasonic power of the ultrasonic treatment is 300 W, and the ultrasonic treatment time is 20 minutes.

[0037] The mass fraction of the lanthanum chloride solution of the present embodiment is 3%.

[0038] The preparation method of the modified synergistic agent of this embodiment is: S101: heat treating the carbon nanotubes at 210°C for 10 min, then cooling to 60°C at a rate of 1°C / min, and keeping the temperature; S102: preparing a 2% by weight sodium dodecylbenzene sulfonate solution and a 5% by weight chitosan solution; adding 2 parts by weight of the sodium dodecylbenzene sulfonate solution to 5 parts by weight of the chitosan solution, and then adding 2 parts by weight of alginate, and stirring thoroughly to obtain a coordinated solution; S103: The carbon nanotubes treated in S101 and the co-formulation liquid are stirred and treated in a weight ratio of 3:7, and then filtered and dried to obtain a modified co-formulation agent.

[0039] The diameter of the carbon nanotubes in this embodiment is 1 nm.

[0040] Example 2 A method for improving the corrosion resistance of an aluminum anodized film according to the present embodiment comprises the following steps: Step 1: Laser purifies the surface of the aluminum anode: the laser transmitter focuses the laser beam on the surface of the aluminum anode for cleaning and purification. The average power of the laser transmitter is 300W, the adjustable range of the pulse frequency is 2000KHz, the pulse width is 300ns, and the single pulse energy is 100mJ. Step 2: The aluminum anode purified in step 1 is repaired by using aluminum powder as raw material through powder spreading and laser scanning, with laser power of 650W, scanning spot diameter of 70um, scanning speed of 7000mm / s and scanning spacing of 0.2mm; Step 3: quench the aluminum anode repaired in step 2 at a quenching temperature of 150°C for 5 hours, then place the quenched aluminum anode in an electrolyte for coating, then take it out for water washing at a water washing temperature of 80°C, and finally quickly dry it at 100°C for 1 minute; The electrolyte comprises the following raw materials in parts by weight: 25 parts by weight of sulfuric acid, 11 parts by weight of silica sol, 9 parts by weight of balancing agent, 8 parts by weight of oxalic acid, 6 parts by weight of modifying co-forming agent, and 20 parts by weight of water.

[0041] The coating treatment in this embodiment uses an aluminum anode as the anode and an aluminum alloy plate as the cathode, and the ratio of the cathode to the anode area is 2:1. The anodic coating oxidation is performed for 60 minutes at a temperature of 30°C and a DC current of 15-20An.

[0042] The preparation method of the balancing agent of this embodiment is: S01: The graphene is first placed in a sufficient amount of 5% by mass hydrogen peroxide solution and stirred sufficiently, then washed with water and dried, and then stirred sufficiently in a sufficient amount of 4% by mass potassium permanganate solution, then washed with water and dried; S02: immersing the hydroxyapatite in a 3% yttrium nitrate solution with a mass fraction of 5 times the total amount of hydroxyapatite and stirring thoroughly to obtain a hydroxyapatite solution; 3 parts by weight of sodium carboxymethyl cellulose, 2 parts by weight of silane coupling agent and 5 parts by weight of hydroxyapatite liquid are uniformly mixed, and then 3 parts by weight of sodium silicate solution is added and stirred continuously to obtain a modified liquid; S03: preheating the graphene dried in S01 to 65°C, and then immersing it in a modification liquid 5 times the total amount of the graphene, stirring and modifying it, and after the stirring is completed, a modified graphene liquid is obtained; S04: The modified graphene liquid and the rare earth-doped nano-titanium dioxide modifier are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a balancing agent.

[0043] The mass fraction of the sodium silicate solution is 6%; the silane coupling agent is silane coupling agent KH550.

[0044] The stirring speed of the stirring modification treatment in this embodiment is 400 r / min, and the stirring is for 1 hour.

[0045] The preparation method of the rare earth-doped nano-titanium dioxide modifier of this embodiment is as follows: The nano-titanium dioxide was first irradiated in a proton irradiation box for 15 minutes at an irradiation power of 350W. After the irradiation was completed, the irradiated nano-titanium dioxide, lanthanum chloride solution and sodium stearate were prepared in a weight ratio of 3:5:1 to obtain a nano-titanium dioxide agent; 4 parts by weight of boron nitride and 3 parts by weight of cerium oxide are mixed and sintered to obtain a sintering agent. The sintering agent and nano-titanium dioxide agent are ultrasonically treated in a weight ratio of 2:5, and then filtered and dried to obtain a rare earth-doped nano-titanium dioxide modifier.

[0046] The sintering temperature of the sintering treatment in this embodiment is 185° C., and the sintering time is 1 hour; the ultrasonic power of the ultrasonic treatment is 350 W, and the ultrasonic treatment time is 20 minutes.

[0047] The mass fraction of the lanthanum chloride solution of the present embodiment is 5%.

[0048] The preparation method of the modified synergistic agent of this embodiment is: S101: heat treating the carbon nanotubes at 220°C for 10 min, then cooling to 60°C at a rate of 3°C / min, and keeping the temperature; S102: preparing a 5% by weight sodium dodecylbenzene sulfonate solution and a 5% by weight chitosan solution; adding 4 parts by weight of the sodium dodecylbenzene sulfonate solution to 8 parts by weight of the chitosan solution, and then adding 5 parts by weight of alginate, and stirring thoroughly to obtain a coordinated solution; S103: The carbon nanotubes treated in S101 and the co-formulation liquid are stirred and treated in a weight ratio of 3:7, and then filtered and dried to obtain a modified co-formulation agent.

[0049] The diameter of the carbon nanotubes in this embodiment is 2 nm.

[0050] Example 3 A method for improving the corrosion resistance of an aluminum anodized film according to the present embodiment comprises the following steps: Step 1: Laser purifies the surface of the aluminum anode: the laser transmitter focuses the laser beam on the surface of the aluminum anode and moves it for cleaning and purification. The average power of the laser transmitter is 300W, the adjustable range of the pulse frequency is 2000KHz, the pulse width is 300ns, and the single pulse energy is 75mJ. Step 2: The aluminum anode purified in step 1 is repaired by using aluminum powder as raw material through powder spreading and laser scanning, with laser power of 650W, scanning spot diameter of 70um, scanning speed of 7000mm / s and scanning spacing of 0.2mm; Step 3: quench the aluminum anode repaired in step 2 at a quenching temperature of 150°C for 5 hours, then place the quenched aluminum anode in an electrolyte for coating, then take it out for water washing at a water washing temperature of 80°C, and finally quickly dry it at 100°C for 1 minute; The electrolyte comprises the following raw materials in parts by weight: 22.5 parts by weight of sulfuric acid, 9 parts by weight of silica sol, 7.5 parts by weight of balancing agent, 6.5 parts by weight of oxalic acid, 5 parts by weight of modifying co-forming agent, and 17.5 parts by weight of water.

[0051] The coating treatment in this embodiment uses an aluminum anode as the anode and an aluminum alloy plate as the cathode, and the ratio of the cathode to the anode area is 2:1. The anodic coating oxidation is performed for 60 minutes at a temperature of 30°C and a DC current of 15-20An.

[0052] The preparation method of the balancing agent of this embodiment is: S01: The graphene is first placed in a sufficient amount of 5% by mass hydrogen peroxide solution and stirred sufficiently, then washed with water and dried, and then stirred sufficiently in a sufficient amount of 4% by mass potassium permanganate solution, then washed with water and dried; S02: immersing the hydroxyapatite in a 3% yttrium nitrate solution with a mass fraction of 3.5 times the total amount of hydroxyapatite and stirring thoroughly to obtain a hydroxyapatite solution; 2 parts by weight of sodium carboxymethyl cellulose, 1.5 parts by weight of silane coupling agent and 3.5 parts by weight of hydroxyapatite liquid are uniformly mixed, and then 2.5 parts by weight of sodium silicate solution is added and stirred continuously to obtain a modified liquid; S03: preheating the graphene dried in S01 to 65°C, and then immersing it in a modification liquid of 4 times the total amount of graphene, stirring and modifying it, and after the stirring is completed, a modified graphene liquid is obtained; S04: The modified graphene liquid and the rare earth-doped nano-titanium dioxide modifier are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1250 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a balancing agent.

[0053] The mass fraction of the sodium silicate solution is 4.5%; the silane coupling agent is silane coupling agent KH550.

[0054] The stirring speed of the stirring modification treatment in this embodiment is 375 r / min, and the stirring is for 1 hour.

[0055] The preparation method of the rare earth-doped nano-titanium dioxide modifier of this embodiment is as follows: The nano-titanium dioxide was first irradiated in a proton irradiation box for 12.5 minutes at an irradiation power of 350 W. After the irradiation was completed, the irradiated nano-titanium dioxide, lanthanum chloride solution and sodium stearate were prepared in a weight ratio of 3:5:1 to obtain a nano-titanium dioxide agent; 3 parts by weight of boron nitride and 2 parts by weight of cerium oxide are mixed and sintered to obtain a sintering agent. The sintering agent and nano-titanium dioxide agent are ultrasonically treated in a weight ratio of 2:5, and then filtered and dried to obtain a rare earth-doped nano-titanium dioxide modifier.

[0056] The sintering temperature of the sintering treatment in this embodiment is 180° C., and the sintering time is 1 hour; the ultrasonic power of the ultrasonic treatment is 325 W, and the ultrasonic treatment time is 20 minutes.

[0057] The mass fraction of the lanthanum chloride solution of the present embodiment is 4%.

[0058] The preparation method of the modified synergistic agent of this embodiment is: S101: heat treating the carbon nanotubes at 215°C for 10 min, then cooling to 60°C at a rate of 2°C / min, and keeping the temperature; S102: preparing a 3.5% by weight sodium dodecylbenzene sulfonate solution and a 5% by weight chitosan solution; adding 3 parts by weight of the sodium dodecylbenzene sulfonate solution to 6.5 parts by weight of the chitosan solution, and then adding 3.5 parts by weight of alginate, and stirring thoroughly to obtain a coordinated solution; S103: The carbon nanotubes treated in S101 and the co-formulation liquid are stirred and treated in a weight ratio of 3:7, and then filtered and dried to obtain a modified co-formulation agent.

[0059] The diameter of the carbon nanotubes in this embodiment is 1.5 nm.

[0060] Comparative Example 1 The difference from Example 3 is that no balancing agent is added to the electrolyte.

[0061] Comparative Example 2 The difference from Example 3 is that no modified graphene liquid is added to the balancing agent.

[0062] Comparative Example 3 The difference from Example 3 is that no preheated graphene is added to the modified graphene liquid.

[0063] Comparative Example 4 The difference from Example 3 is that the modified graphene liquid is not modified by a modifying liquid.

[0064] Comparative Example 5 The difference from Example 3 is that no hydroxyapatite liquid is added to the modified liquid.

[0065] Comparative Example 6 The difference from Example 3 is that no silane coupling agent and sodium silicate solution are added to the modified liquid.

[0066] Comparative Example 7 The difference from Example 3 is that no modifier for preparing nano titanium dioxide doped with rare earth is added to the balancing agent.

[0067] Comparative Example 8 The difference from Example 3 is that no modifying co-formulator is added to the electrolyte.

[0068] Comparative Example 9 The difference from Example 3 is that no co-forming liquid treatment is used in the preparation of the modified co-forming agent.

[0069] Comparative Example 10 The difference from Example 3 is that the nano carbon nanotubes treated in S101 are directly replaced by nano carbon nanotubes.

[0070] The products of Examples 1 to 3 and Comparative Examples 1 to 10 were tested for corrosion resistance (the products were placed in a sodium chloride solution with a mass fraction of 3.5%, the test temperature was 40°C, the surface corrosion of the samples was observed, and the corrosion resistance time was tested), wear resistance and adhesion performance (the products were quenched at 250°C, and the quenching non-blistering time was tested). The performance measurement results are as follows: Adhesion test time between film layer and substrate (min) <![CDATA[Wear amount (mm 3 )]]> Corrosion resistance time (h) Example 1 282 0.03 358 Example 2 284 0.02 362 Example 3 287 0.02 365 Comparative Example 1 223 0.20 302 Comparative Example 2 232 0.13 313 Comparative Example 3 237 0.11 322 Comparative Example 4 235 0.10 327 Comparative Example 5 241 0.07 332 Comparative Example 6 248 0.06 339 Comparative Example 7 228 0.17 318 Comparative Example 8 226 0.18 316 Comparative Example 9 245 0.13 335 Comparative Example 10 240 0.15 327 From Examples 1 to 3 and Comparative Examples 1 to 10, it can be concluded that the adhesion test time between the film layer and the substrate of Example 3 of the present invention can reach 287 minutes, the corrosion resistance time can reach 365 hours, and the wear amount can be as low as 0.02 mm. The adhesion, wear resistance and corrosion resistance of the product can achieve coordinated improvement; Based on the above performance test, the present invention places the product under 1500V DC for 5 minutes to test the product's withstand voltage stability. The test results are as follows: Adhesion test time between film layer and substrate (min) <![CDATA[Wear amount (mm 3 )]]> Corrosion resistance time (h) Example 1 276 0.08 350 Example 2 279 0.07 355 Example 3 283 0.05 359 Comparative Example 1 154 0.87 212 Comparative Example 2 165 0.80 237 Comparative Example 3 172 0.71 249 Comparative Example 4 188 0.65 258 Comparative Example 5 193 0.58 277 Comparative Example 6 202 0.47 289 Comparative Example 7 160 0.83 223 Comparative Example 8 158 0.85 218 Comparative Example 9 193 0.58 287 Comparative Example 10 185 0.64 269 From comparative examples 1-10, embodiment 3 and the withstand voltage test, it can be seen that the product of embodiment 3 still has significant performance stability under withstand voltage conditions; When no balancing agent or modifying synergist is added to the electrolyte, the performance of the product shows a significant trend of deterioration. When the two are used in combination, the product performance effect is most significant. The modified graphene liquid is not added to the balancing agent, the preheated graphene is not added to the modified graphene liquid, the modified graphene liquid is not modified by the modifying liquid, the hydroxyapatite liquid is not added to the modifying liquid, the silane coupling agent and the sodium silicate solution are not added to the modifying liquid, and the modifying agent doped with rare earth to prepare nano titanium dioxide is not added to the balancing agent. The performance of the product has a tendency to deteriorate to varying degrees. The modified graphene liquid obtained by the specific method of the present invention and the preheated graphene has the most significant product performance effect. At the same time, the modifying agent doped with rare earth to prepare nano titanium dioxide is not added to the balancing agent, and the performance of the product has a more obvious tendency to deteriorate. The balancing agents obtained by different methods have a tendency to deteriorate to varying degrees. In the preparation of the modified synergistic agent, the carbon nanotubes that were not treated with the synergistic liquid and S101 were directly replaced by carbon nanotubes, and the performance of the products showed a trend of deterioration. The modified synergistic agent obtained by the method of the present invention had the most significant product performance effect.

[0071] The present invention further explores the product performance by doping rare earth to prepare a nano titanium dioxide modifier; Experimental Example 1 The same as Example 3, the only difference is that no sintering agent is added in the preparation of the modifier of rare earth-doped nano-titanium dioxide.

[0072] Experimental Example 2 The same as Example 3, except that no boron nitride is added to the sintering agent.

[0073] Experimental Example 3 The same as Example 3, except that cerium oxide is not added to the sintering agent.

[0074] Experimental Example 4 The same as Example 3, the only difference is that no irradiated nano titanium dioxide is added in the preparation of the nano titanium dioxide agent.

[0075] Experimental Example 5 The same as Example 3, the only difference is that no sodium stearate and lanthanum chloride solution are added in the preparation of the nano titanium dioxide agent, and water is used instead.

[0076] Based on the withstand voltage test conditions, the performance tests of Experimental Examples 1 to 5 are as follows: Adhesion test time between film layer and substrate (min) <![CDATA[Wear amount (mm 3 )]]> Corrosion resistance time (h) Experimental Example 1 172 0.75 247 Experimental Example 2 192 0.57 283 Experimental Example 3 215 0.47 313 Experimental Example 4 188 0.63 276 Experimental Example 5 249 0.23 338 It can be seen from Experimental Examples 1 to 5 that no sintering agent is added in the preparation of the rare earth-doped nano-titanium dioxide modifier. Among the preparation factors of the rare earth-doped nano-titanium dioxide modifier, the product performance deterioration is the most obvious, followed by the nano-titanium dioxide agent not adding irradiated nano-titanium dioxide in the preparation, while no boron nitride is added to the sintering agent, no cerium oxide is added to the sintering agent, and no sodium stearate and lanthanum chloride solution are added in the preparation of the nano-titanium dioxide agent. Water is used instead, and the performance of the products has a tendency to deteriorate. Only the sintering agent prepared by the method of the present invention is combined with the nano-titanium dioxide agent of the present invention, the performance effect of the product is the most significant. In the preparation of the sintering agent, the raw materials are indispensable. Only by using the specific raw material ratio of the present invention, the use of other raw material ratios is not as significant as the effect of the present invention.

[0077] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0078] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for improving the corrosion resistance of anodized aluminum film, characterized in that: The following steps are involved: Step 1: Laser purifies the surface of the aluminum anode: the laser transmitter focuses the laser beam on the surface of the aluminum anode and moves it for cleaning and purification. The average power of the laser transmitter is 300W, the adjustable range of the pulse frequency is 2000KHz, the pulse width is 300ns, and the single pulse energy is 50~100mJ; Step 2: The aluminum anode purified in step 1 is repaired by using aluminum powder as raw material through powder spreading and laser scanning, with laser power of 650W, scanning spot diameter of 70um, scanning speed of 7000mm / s and scanning spacing of 0.2mm; Step 3: quench the aluminum anode repaired in step 2 at a quenching temperature of 150°C for 5 hours, then place the quenched aluminum anode in an electrolyte for coating, then take it out for water washing at a water washing temperature of 80°C, and finally quickly dry it at 100°C for 1 minute; The electrolyte It includes the following raw materials in parts by weight: 20-25 parts by weight of sulfuric acid, 7-11 parts by weight of silica sol, 6-9 parts by weight of balancing agent, 5-8 parts by weight of oxalic acid, 4-6 parts by weight of modifying co-compounding agent, and 15-20 parts by weight of water.

2. The method for improving the corrosion resistance of anodized aluminum film according to claim 1, characterized in that: The coating treatment uses an aluminum anode as an anode and an aluminum alloy plate as a cathode, and the ratio of the cathode to the anode area is 2:

1. Anodic coating oxidation is performed for 60 minutes under the conditions of a temperature of 30° C. and a direct current of 15-20 An.

3. The method for improving the corrosion resistance of anodized aluminum film according to claim 1, characterized in that: The preparation method of the balancing agent is: S01: The graphene is first placed in a sufficient amount of 5% by mass hydrogen peroxide solution and stirred sufficiently, then washed with water and dried, and then stirred sufficiently in a sufficient amount of 4% by mass potassium permanganate solution, then washed with water and dried; S02: immersing the hydroxyapatite in a 3% yttrium nitrate solution having a mass fraction of 2 to 5 times the total amount of the hydroxyapatite and stirring sufficiently to obtain a hydroxyapatite solution; 1-3 parts by weight of sodium carboxymethyl cellulose, 1-2 parts by weight of silane coupling agent and 2-5 parts by weight of hydroxyapatite liquid are uniformly mixed, and then 2-3 parts by weight of sodium silicate solution are added and stirred continuously to obtain a modified liquid; S03: preheating the graphene dried in S01 to 65°C, and then immersing it in a modification liquid 3 to 5 times the total amount of graphene, stirring and modifying it, and after the stirring is completed, a modified graphene liquid is obtained; S04: The modified graphene liquid and the rare earth-doped nano-titanium dioxide modifier are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a balancing agent.

4. The method for improving the corrosion resistance of anodized aluminum film according to claim 3, characterized in that: The mass fraction of the sodium silicate solution is 3-6%; the silane coupling agent is silane coupling agent KH550.

5. The method for improving the corrosion resistance of anodized aluminum film according to claim 3, characterized in that: The stirring speed of the stirring modification treatment is 350-400 r / min, and the stirring is for 1 hour.

6. The method for improving the corrosion resistance of anodized aluminum film according to claim 3, characterized in that: The preparation method of the rare earth-doped nano-titanium dioxide modifier is as follows: The nano-titanium dioxide is first irradiated in a proton irradiation box for 10 to 15 minutes at an irradiation power of 350 W. After the irradiation is completed, the irradiated nano-titanium dioxide, lanthanum chloride solution and sodium stearate are prepared in a weight ratio of 3:5:1 to obtain a nano-titanium dioxide agent; 2-4 parts by weight of boron nitride and 1-3 parts by weight of cerium oxide are mixed and sintered to obtain a sintering agent. The sintering agent and nano-titanium dioxide agent are ultrasonically treated in a weight ratio of 2:5, and then filtered and dried to obtain a rare earth-doped nano-titanium dioxide modifier.

7. The method for improving the corrosion resistance of anodized aluminum film according to claim 6, characterized in that: The sintering treatment has a sintering temperature of 175-185° C. and a sintering time of 1 hour. The ultrasonic treatment has an ultrasonic power of 300-350 W and a ultrasonic time of 20 minutes.

8. The method for improving the corrosion resistance of anodized aluminum film according to claim 6, characterized in that: The mass fraction of the lanthanum chloride solution is 3-5%.

9. The method for improving the corrosion resistance of anodized aluminum film according to claim 1, characterized in that: The preparation method of the modified synergistic agent is: S101: heat treating the carbon nanotubes at 210-220°C for 10 min, then cooling to 60°C at a rate of 1-3°C / min, and keeping the temperature; S102: preparing a 2-5% by mass sodium dodecylbenzene sulfonate solution and a 5% by mass chitosan solution; Add 2 to 4 parts by weight of sodium dodecylbenzene sulfonate solution to 5 to 8 parts by weight of chitosan solution, then add 2 to 5 parts by weight of alginic acid, and stir thoroughly to obtain a coordinated solution; S103: The carbon nanotubes treated in S101 and the co-formulation liquid are stirred and treated in a weight ratio of 3:7, and then filtered and dried to obtain a modified co-formulation agent.

10. The method for improving the corrosion resistance of anodized aluminum film according to claim 9, characterized in that: The diameter of the nano carbon nanotube is 1-2 nm.